Zastosowanie projektu edukacyjnego w pracy z dziećmi w wieku wczesnoszkolnym w refleksjach i działaniach przyszłych nauczycieli - Agnieszka Kaczor (Problemy Wczesnej Edukacji)
The article reflects on the possibility of using an educational project in working with a child of early school age. The theoretical basis for the research was the recognition of the importance of the project method for the learning process of children from grades I–III. Based on a qualitative analysis of student studies, the practical and methodological dimension of the application of an educational project when working with children from grades I–III was shown. It was noticed that the use of an educational project in work with children of preschool and early school age promotes the integral development of small researchers. Personal involvement of children in project activities translates into positive motivation to work and obtained results in the form of knowledge and skills. In addition, the use of the project method in educational practice can be considered one of the ways of breaking automatism in didactic work and stimulating the teacher to creatively fulfill the professional role.